Inovação institucional no contexto do federalismos brasileiro pós-1988: a emenda constitucional no. 29 de 2000 e os governos estaduais. - Fatima Beatriz Carneiro Teixeira P. Fortes (2008)
The purpose of this thesis is to investigate the effects of Constitutional Amendment 29 (EC n.29), of 2000, on the decisions of state governors related to the allocation of funds for the health sector, aiming at identifying its conditioning factors. Two main analytical arguments guided the analysis. The first: institutions, understood as formal rules, orientate the calculations and the interaction of actors. The second: in order to investigate its impacts, it is necessary to consider the importance of human agency and that choices reflect the interaction between institutions and conditions. In fact, after the passing of Amendment 29, the great majority of the states increased their revenue percentage invested in the health sector, differently from what was seen in the previous period. It was also a fact that the behavior of the states significantly varied. Such variability regarding the governors´ responses instigated the investigation into the possible factors that condition their behavior. Even recognizing that the relation between conditioning factors and decision-making is extremely complex, the assumption was that, based on the association between variables capable of reflecting the diversity of Brazilian states concerning political, economical and social aspects and the governors´ responses regarding expenditures on health, it would be possible to answer the main proposed question. The results of the adjusted model showed that the variable amendment indicating the passing of EC n.29 was highly significant, confirming that its passing induced governors to raise the revenue percentage invested in the health sector. Among context-related variables, just the net per capita revenue and the ideological profile of the governor´s party were significant. However, the overall results allow to state that such variables only marginally condition the substantial effect of the Amendment on the states. What can be concluded is that the introduction of a rule such as EC n.29 was capable of inducing governors to adopt behaviors despite the context-related variables considered herein. Although the selected variables may compose the context of choice, their influences, mediated by all sorts of interests and circumstances, could not be captured in such an approach. The study also attempted to call attention to the fact that, while inducing the increase in the expenditures on health, EC n.29 started to stimulate other games involving disputes related to the concept of health actions and services and concerning the calculation basis that define the participation of the federal entity. In this regard, the present study confirmed the pertinence of the neo-institutionalism argument which states that institutions can not be considered only as inherited coercions and, thus, exogenous to the political process, but that rational actors tend to seek the participation in the elaboration/alteration of rules, so as to favor their choices. The investigation brought light as well to the challenges of responsibility sharing set by federative engineering. Although the Amendment was, in a way, well-succeeded in the sense that it imposed a certain direction to expenditures on health, it was possible to see that some states reduced the revenue percentage invested in the health sector when it should have been increased, and that only a few states managed to reach the established minimum of 12% in 2004. Therefore, even though collective actions in federative countries can be favored by means of rules, their full effects may be delayed or even not be reached if consensus on them turns out to be fragile. In case of EC n.29, such fragility is manifested by the drawbacks faced in its regulation and implementation.